Psychometric properties of the Italian version of the Speech Handicap Index. Issue 9 (24th April 2021) - Mozzanica, Francesco; Scarponi, Letizia; Rota, Martina; Succo, Giovanni; Crosetti, Erika; Guzzo, Marco; Bossi, Paolo; Piazza, Cesare; Ottaviani, Francesco; Schindler, Antonio
Abstract: Objective: Speech impairment is common in patients affected by head and neck cancer and impact on quality of life. Therefore, specific instruments are required for its evaluation. The aim of this study is to evaluate the psychometric properties of the Italian Speech Handicap Index. Methods: Data were obtained from 50 patients and 75 asymptomatic subjects. The study consisted of five phases: (1) item generation, (2) internal consistency and reliability analysis, (3) normative data generation, (4) validity analysis, performed by comparing the Italian Speech Handicap Index scores obtained in patients and asymptomatic subjects, and by correlating its scores with the results of the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Head and Neck Module, and (5) cut-off value. Results: Internal consistency was good (Cronbach α  = 0.9) and the test–retest reliability was strong. A significant difference in Italian Speech Handicap Index total score between patients and asymptomatic subjects was found. Moderate correlations between the two questionnaires were observed. A cut-off value of 14.5 demonstrated a sensitivity of 96% and a specificity of 100%. Conclusion: The Italian Speech Handicap Index is a reliable and valid clinical tool. Its application in everyday practice and outcome research is recommended. IMPLICATIONS FOR REHABILITATION: Rehabilitation of speech in head and neck cancer patients is frequently needed, especially after surgical treatment. Speech impairment represents one of the most essential factors influencing the quality of life in head and neck cancer patients. The evaluation of the speech impairment should be performed using dedicated assessment tools.